Economic burden of multidrug-resistant bacteria in nursing homes in Germany: a cost analysis based on empirical data. Issue 2 (23rd February 2016) - Huebner, Claudia; Roggelin, Marcus; Flessa, Steffen
Abstract : Objectives: Infections and colonisations with multidrug-resistant organisms (MDROs) increasingly affect different types of healthcare facilities worldwide. So far, little is known about additional costs attributable to MDROs outside hospitals. The aim of this study was to analysis the economic burden of multidrug-resistant bacteria in nursing homes in Germany. Setting: The cost analysis is performed from a microeconomic perspective of the healthcare facilities. Study took place in six long-term care facilities in north-eastern Germany. Participants: Data of 71 residents with a positive MDRO status were included. Primary and secondary outcome measures: The study analysed MDRO surveillance data from 2011 to 2013. It was supplemented by an empirical analysis to determine the burden on staff capacity and materials consumption. Results: 11 793 days with a positive multidrug-resistant pathogen diagnosis could be included in the analysis. On average, 11.8 (SD±6.3) MDRO cases occurred per nursing home. Mean duration per case was 163.3 days (SD±97.1). The annual MDRO-related costs varied in nursing homes between €2449.72 and €153 263.74 on an average €12 682.23 per case. Main cost drivers were staff capacity (€43.95 per day and €7177.04 per case) and isolation materials (€24.70 per day and €4033.51 per case). Conclusions: The importance of MDROs in nursing homes could be confirmed. MDRO-related cost data in this specific healthcare sector were collected for the first time. Knowledge about the burden of MDROs will enable to assess the efficiency of hygiene intervention measures in nursing homes in the future.